English only or more?: Language ideologies of international students in an EMI university in multilingual Hong Kong. Issue 3 (27th May 2022) - Sung, Chit Cheung Matthew
ABSTRACT: This paper investigates the language ideologies held by a group of international students in an English medium instruction (EMI) university in multilingual Hong Kong. The findings indicate that the participants' beliefs about English extend beyond its role as an instructional medium and encompass its use as a lingua franca and as a means of social inclusion. It is also found that the participants hold complex yet sometimes contradictory ideologies about the kinds of English to be used and/or accepted and about the monolingual and multilingual uses of English in the EMI university context. Taken together, the study suggests that the participants' ideologies with respect to the roles of English and the norms of English use in the EMI university context are much more complex than what language policy from above suggests. The findings also reveal the ideological tensions over the norms of English use in the EMI university context and the closely intertwined relationship between the participants' language ideologies and the maintenance of their interests, especially in relation to access to learning opportunities in the classroom. The study calls for attention to broader issues pertaining to social inclusion/exclusion, linguistic advantage/disadvantage and educational equality/inequality in the multilingual EMI university context.